Analisis dan Implementasi Restful API guna Pengembangan Sistem Informasi Akademik pada Perguruan Tinggi - Novianto, Mohammad Akmaluddin; Munir, Sirojul (Jurnal Informatika Terpadu, 2022)
In an organization, one of the most important is the processing of data and information, with the larger and complexity of an information system, the need for data processing and integration is a big concern for many organizations. STT-NF now has started to utilize technology and develop applications to support the ease of academic community. One of the applications developed is a mobile-based academic information system application. Currently STT-NF already has an academic system called AIS with a web platform located in ais.nurulfikri.ac.id. However, there is a problem when the academic information system will be developed in STT Terpadu Nurul Fikri with a platform or with a different programming language, the problem is the unavailability of web services that are able to integrate the system with other systems to be developed, thus complicating development, especially in terms of exchange, integration and processing of data. Therefore, it is necessary to design and create the service (web service) to solve the difficulties experienced by the AIS system. This study will design and create a web service API study result card module for academic information system mobile applications in STT NF using RESTful – Spring Framework, which in addition to providing services for other systems in need, also offers the ease of bridging data exchange without any concerns about the differences in platforms and programming languages. Design web service module KHS using waterfall development method, waterfall aims to produce a software or system that has been determined with the best quality. Waterfall prioritizes interaction with stakeholders at the beginning of the project to get a clear picture, and when using the waterfall process, each team completes a stage, then the team must advance to the next stage and be expected without repeating the previous process.